An empirical study of career plateau among auditors in Singapore. - Hou, Sook Min. (2008)
This is a study done on auditors in Singapore to examine the operationalizations of career plateau as well as its effect on work outcomes like intention to quit, career planning and satisfaction. 169 questionnaire surveys were collected from the interviewed firms. The data collected were analysed using simple statistical methods like Pearson correlation, hierarchical regression and factor analysis. The results collected indicated that the perceptual measure of career plateau accounted for more explained variance in the work outcomes, and that career planning, intention to quit and satisfaction correlated negatively with career plateau. The study also introduced the construct of professional plateau, and found that it also accounts for significant variances in the work outcome. The research has indicated that the use of a perceptual measure ( in career plateau as well as perceptual tenure ) is important in examining career plateau of auditors.